The old man's prayer: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story follows an elderly man's heartfelt prayer for his community, illustrating the power of sincere supplication and compassion. It conveys the message that prayer can bring hope and positive change to those around us.